Acute effects of different types of training on dorsal and lumbar spine in expert tennis players - Bonavolonta, V.; Franciosi, E.; Tito, A.; Gallotta, M. C.; Emerenziani, G. P.; Guidetti, L.; Baldari, C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Scoliosis has been found in up to 80% of athletes with an asymmetric load on the trunk and shoulders, such as javelin throwers and tennis players (Swärd, 1992). Further research found asymmetry in volume between dominant and nondominant upper limbs larger in young tennis players than in control group (Rogowski et al., 2008). Anyway it is not clear the relationship between scoliosis and the practice of tennis. In order to investigate this topic, aim of the present study was to evaluate the dorsal-lumbar spine of expert tennis players before and after two different types of training session. Methods The sample consisted of 10 expert tennis players (male n=6, female n=4, age 22.6 ± 1.5 years). We assessed back surface by rasterstereography analysis with Formetric® 3D System (Diers, Germany) before and after two different training sessions both lasting 1 hour and half. The first one was a standard training session and the second was a specific over-shoulder shots training session. Lordotic angle, kiphotic angle, trunk imbalance, pelvic torsion and surface rotation parameters were measured and recorded both in static (S) and in average (A) (longer interval of time) modality. Results In the S modality, lordotic angle was affected by type of training (P<0.01) and by the interaction between training and time (P=0.05). In the A modality, trunk imbalance and pelvic torsion was affected by time (P=0.05), and surface rotation significantly differed for training (P=0.05). Discussion In the S modality we found a significant difference for lordotic angle, supporting the idea that over-shoulder load leads to high stress for the spine, as it links the shoulder and the lower extremity transferring much of the ground reactive forces into the upper extremity and it is also capable of generating additional forces to the throwing motion on its own (Young et al., 1996). For the A modality, our expectation to find more differences, as the recording interval is longer, was confirmed, and we found that 2 of the 3 significant parameters (trunk imbalance and pelvic torsion) were time sensitive and did not change depending on the type of training session; this, could be related just to the load stress that is certainly higher after each training session. Instead, surface rotation was affected by the factor training session, possibly because it indicates the orientation of the spinous process rotation, and the over-shoulder shots such as service are also related to vertebral trunk rotation (Elliot, 2006). References Elliot B, (2006). Br J Sports Med, 40, 392-396. Rogowski I, Ducher G, Brosseau O, Hautier C. (2008). Pediatr Exerc Sci, 20, 263-272. Swärd L. (1992). Sports Med, 13(5), 357-364. Young JL , Herring SA, Press JM, Casazza BA. (1996) J Musculoskeletal Rehabil, 7, 5-17.